Description of Suicide Idea in Among High School Students - Putu Diah Wilya Dewi; Ni Made Dian Sulistiowati; Ni Komang Ari Sawitri; Putu Ayu Emmy Savitri Karin; Putu Sri Febriyanti (Talenta Publisher, 2023)
Complex development and changes in adolescence led to positive or negative effects in terms of how individuals adapt with growth period. This study aims to determine the description of suicidal ideation among adolescent. Involving 317 high school students in Badung Regency, conducted in January 2023 with purposive sampling technique. Data collection was conducted through the Suicide Ideation Scale questionnaire which was distributed through a google form link. This instrument is divided into two aspects namely overt and covert. The results showed that there were 4 (1.2%) grade XI students in Badung Regency who had suicidal ideation, consisting of 3 female students (0.9%) and 1 male student (0.3%). The data shows that students have low suicidal ideation of 1.3%, while those who do not have suicidal ideation are 98.7%. Compared to male students, suicidal ideation was experienced more by female students with a total of 3 people (0.9%). The majority of students are female, namely 195 people (61.5%) while 122 male students (38.5%). The age of students is dominated by students aged 17 years, as many as 311 people (98.1%). The majority of students who became respondents were the second child, with 137 people (43.2%), 125 people (39.4%) had 2 siblings and only 1 person (0.3%) had 6 siblings. On average, students have parents who are still intact, with a total of 290 people (91.5%). The score on the covert aspect was higher than the overt, which means that many students did not show others that they had suicidal thoughts.